1979
DOI: 10.1159/000194030
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Modifications of Pulmonary Surfactant after Bromhexine Derivate Injection

Abstract: The authors study the influence of bromhexine metabolite VIII on phosphohpid and fatty acid composition comparatively to controls, The subcutaneous injection of NA 872 produces on pulmonary surfactant an increase of 43% of total phospholipids. This change in the distribution of phospholipids is shown by the increase of 53% of phosphatidylcholines. A rise of 61.9–74.4% of palmitic acid appears in the phosphatidylcholines of the pulmonary surfactant. It can be noticed that the specific activity of the phosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Animal studies showed that it enhances both bronchial glandular cell secretions [1 ] and the production of alveolar type II pneumocyte surfactant [2][3][4][5][6][7][8]. It also stimu lates ciliary motility [9,10] and accelerates mucociliary transport [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies showed that it enhances both bronchial glandular cell secretions [1 ] and the production of alveolar type II pneumocyte surfactant [2][3][4][5][6][7][8]. It also stimu lates ciliary motility [9,10] and accelerates mucociliary transport [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Increased total phospholipid concen trations were found in lung lavage of rab bits treated with ambroxol [15].…”
Section: Influence O F Ambroxol On the Surfactant Systemmentioning
confidence: 94%
“…[I2]and Prevost et al [15] measured increased specific ac tivity. As specific activity means the ratio of freshly incorporated activity over total concentration of a specific phospholipid (pool size), a decrease should be expected in the case of phospholipase inhibition.…”
Section: Influence O F Ambroxol On the Surfactant Systemmentioning
confidence: 99%
“…The fact that acebrophylline induced the uptake not only of labeled choline but also of 32 Pphosphate suggests it acts on two levels on surfactant synthesis: the first involves ambroxol's estab- lished action on phosphocholine-cytidyl-transferase [25,26] and the second probably because of theophylline-7 acetic acid's action on choline-kinase [22] (fig. 3).…”
Section: ) Synthesis and Release Of Pulmonary Surfactantmentioning
confidence: 99%